„We Put Down Roots on a Branch” — Floristic Motif(s) in the Poetic Work of Anna Frajlich - Fiedeń-Kułak, Anna (The Motifs of Fauna and Flora in Literature and Culture, 2018)
Flora is one the most important motifs in the poetic work of Anna Frajlich. The object of this article is to demonstrate its presence, with the goal of presenting the literary means the poet uses, with the intention of determining their functions.In the lyrical poetry analysed, the motif of flora constitutes the background for the events. Detailed elements of nature are employed as symbols or also mechanisms of biological behaviour are a basis for the presentation of deeper meanings. These in turn are focused on topics such as emigration, rootedness, love, the past and passing, revival, a writer’s credo, the advance of civilization, the role of the individual in history and biologism.